Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1029/2000je001368
|View full text |Cite
|
Sign up to set email alerts
|

Chemical variation of the large Apollo 15 olivine‐normative mare basalt rock samples

Abstract: Abstract. Most chemical analyses of Apollo 15 olivine-normative mare basalts have been conducted on subsamples of <1 g, and dominantly rather less than 0.5 g, very small by the standards of analyses of terrestrial rocks. Most analyses have been partial (a small number of elements) rather than comprehensive. They show considerable scatter, but the general inference has been that the rock samples represent a single suite dominated by olivine control. However, because of the scatter, some workers have suggested m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 23 publications
1
39
0
Order By: Relevance
“…The coarse-grained nature of MIL 05035 requires a large amount of sample for a representative bulk rock analysis, as suggested previously for other coarsely crystalline mare basalts (e.g., Ryder and Schuraytz 2001). Previous studies on MIL 05035 have already demonstrated compositional variation in bulk rock compositions, due to the coarse-grain size (Arai et al 2007;Joy et al 2007Joy et al , 2008Korotev and Zeigler 2007).…”
Section: Bulk Rock Compositionsmentioning
confidence: 81%
“…The coarse-grained nature of MIL 05035 requires a large amount of sample for a representative bulk rock analysis, as suggested previously for other coarsely crystalline mare basalts (e.g., Ryder and Schuraytz 2001). Previous studies on MIL 05035 have already demonstrated compositional variation in bulk rock compositions, due to the coarse-grain size (Arai et al 2007;Joy et al 2007Joy et al , 2008Korotev and Zeigler 2007).…”
Section: Bulk Rock Compositionsmentioning
confidence: 81%
“…Sample masses for chemical analyses of martian meteorites (when given) are typically 100-500 mg, and this is generally too small to yield representative analyses of crystalline basalt rocks (Ryder and Schuraytz 2001). This problem is exacerbated for the most incompatible trace elements, which are concentrated in small, dispersed mineral grains or melt pockets.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Primitive Apollo 12 and 15 basalts that have been suggested to represent parental compositions for their particular petrographic suites (olivine, pigeonite and ilmenite basalts), have MgO ranging from 8 to 13 wt% (Neal et al, 1994;Ryder and Schuraytz, 2001;Snyder et al, 1997). Thermodynamic modeling of the crystallization sequence of primitive low-Ti Apollo 12 and 15 olivine basalts such as 12009, 12072 and 15555, using the MELTS and MAGFOX codes yield major element compositions that match the LAP basalts (Righter et al, 2005).…”
Section: Constraints On the Lap Source Regionmentioning
confidence: 99%